Inscribing the Self in a Changing World: The Poetry of David Mus - Bach, Raymond (Dalhousie French Studies, 2024)
The Franco-American poet, David Mus, who passed away in 2023, produced an impressive body of work in both English and French. His poetry has a down-to-earth quality that is intimately connected to the Burgundian countryside, where he lived for more than fifty years; but this rootedness is counterbalanced by a complex, often elusive, syntax and an inventive use of typography. The result is a unique poetic language that corresponds in both form and content to the poet’s experience of a world that is undergoing constant change; for Mus is above all a poet of motion who seeks to create the poetic equivalent of his physical inscription within the ceaselessly changing landscapes he explores. The poet leaves a physical trace (imprint) and a poetic trace (in-print), though both forms of creation are subject to destruction and renewal. A detailed analysis of Mus’s book-length poem, Saillie (2019), shows how the reader is drawn into repeating the processes of creation, destruction and transformation that characterize both the natural and man-made world; as we navigate the work’s complex series of semantic and syntactic disruptions, we become active participants in the poetic project of inscribing the self simultaneously in the changing world and in the written word.